Penelitian pemetaan struktur intelektual Tax Income dengan pendekatan Bibiometrix dengan Vosviewer - Hidayah, Nurul (Maliki Interdisciplinary Journal, 2024)
The tax system consists of tax revenues, or tax revenues, which serve to determine the tax obligations of individuals and companies. It is critical to understand the intellectual structure of the tax revenue field to develop fair and successful tax policies. The software called Vosviewer is intended to build and visualize bibliometric networks. In this research, VOSviewer is used to analyze and visualize the relationship between keywords in scientific texts about Tax Income. The analysis results show that Tax Income has a strong relationship with pretax and effects, as well as law, economics and development. The VOSviewer map also shows a strong relationship between Tax Income and other keywords such as “Tax Payer” and “Tax Income.” This analysis helps understand how the intellectual structure and trends of tax spending research have changed over time. It also provides an overview of the most researched topics and possible future research topics. This study uses data from 199 international journals accredited by Scopus, as well as mapping data from Publish Or Perish with VOSViewer. A survey of scientific publications on Tax Income from 2014 to 2024 shows increases and decreases every year, especially in the last two years. In addition, this research finds that effective tax rates are not correlated with bank profitability, and that horizontally fair taxation can prevent rent-seeking and ideological conflicts about tax policy.